Spin glasses - Fischer, K. H. (Cambridge University Press, 1990)
The study of spin glasses is a fascinating new topic in condensed matter physics that has attracted considerable attention over recent years. This book gives a comprehensive account of the subject, and will provide a valuable overview and reference to both newcomers and experts in the field. The authors discuss the most important developments in the theory, experimental work and computer modelling of spin glasses. The first chapters give a general introduction to the basic concepts, followed by a discussion of mean field theory, the only well-established spin glass theory so far. This book will be of interest primarily to condensed matter physicists, but because of the potentially wide applications of the theory involved, the book should also appeal to researchers in other disciplines, including theoretical physics, metallurgy and computational neuroscience.